2021
DOI: 10.1002/ccr3.4008
|View full text |Cite
|
Sign up to set email alerts
|

Successful pembrolizumab treatment of microsatellite instability‐high intrahepatic cholangiocarcinoma: A case report

Abstract: Key Clinical Message The tumor reduction effect of pembrolizumab is extremely high compared to standard chemotherapy and might show prolonged survival. Therefore, the MSI status should be examined in patients with cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Only a handful of cases of successful management of advanced CCA with pembrolizumab were reported in the literature (Table 1) [14][15][16][17]. All of these cases included advanced CCA with high MSI status that initially failed the recommended combined chemotherapy but achieved a good response to pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of cases of successful management of advanced CCA with pembrolizumab were reported in the literature (Table 1) [14][15][16][17]. All of these cases included advanced CCA with high MSI status that initially failed the recommended combined chemotherapy but achieved a good response to pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“… 76 Recently, more studies have reported similar dramatic anti-tumour or even complete tumour responses. [77] , [78] , [79] , [80] …”
Section: Preclinical Cca Immunotherapymentioning
confidence: 99%
“…However, almost half of all patients with CCA have immunologically 'cold' tumors and have low response rates to treatment with ICIs (136). Genetic abnormalities in tumor cells, such as defective DNA mismatch repair (dMMR) and microsatellite instability-high (MSI-H), can also influence the responsiveness of tumors to ICIs (137)(138)(139). Studies have suggested that patients with solid tumors that feature abundant CD8 + T cells, significant PD-L1 expression, MSI-H, high levels of dMMR and a high tumor mutation burden (TMB) may exhibit sensitivity to immunotherapy (140,141).…”
Section: Immunotherapy For Cholangiocarcinomamentioning
confidence: 99%